Continued Studies of Vibrational Communication (Drumming) Of North American Plecoptera - Sandberg, John B. (Illiesia, 2006)
The drumming signals of thirteen North American stonefly species are reported.New signals are described for six species (Isoperla muir, I. rainera,I. rougensis, I. tilasqua, Pteronarcys scotti and the female answer ofSoliperla campanula). Descriptions of new signal characters and results fromadditional population locations are provided for seven species (Perlinelladrymo, Hydroperla crosbyi, I. bifurcata, I. sobria, I. phalerata, I. quinquepunctata and Pteronarcys dorsata).
Keywords: insekti; Plecoptera; vrbnice; favna; Severna Amerika